Pengaruh Penggunaan Pendekatan Saintifik Terhadap Kemampuan Pemecahan Masalah Siswa Kelas V Pada Mata Pelajaran PAI Di SD Negeri 04 Birugo Bukittinggi - Afifah Nur Zahra; Supriadi Supriadi; Fajriyani Arsya; Ulva Rahmi (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2023)
This research was motivated by students who had difficulty when faced with problems that were slightly different from the examples given by the teacher. The use of the 2013 curriculum which uses real life as learning becomes a difficulty for students, especially in terms of problem solving abilities. Therefore, to remember the important role of the scientific approach in implementing the 2013 curriculum, the scientific approach allows it to influence students' problem-solving abilities. So this research aims to find out how much influence the "Scientific Approach has on the Problem Solving Ability of Class V Students in PAI Subjects at SD Negeri 04 Birugo Bukittinggi". This research is correlational research with a quantitative approach. The population is 107 students consisting of four classes. The sample consisted of 32 students, with a sampling technique, namely probability sampling. Data was collected using a questionnaire and analyzed using a simple linear regression test.